2013
DOI: 10.18041/1794-5232/cultrua.2013v10n2.3792
|View full text |Cite
|
Sign up to set email alerts
|

Cuidado cultural del diabético amputado

Abstract: Objetivo ldentificar el cuidado émic y el cuidado étic documentado en pacientes con amputación por pie diabético con el fin de plantear los modos de acción-decisión que faciliten un cuidado de Enfermería culturalmente congruente en el hogar de estos pacientes. Metodología Para la descripción del cuidado émic se usaron como técnicas de recolección de información:la observación, las notas de campo y las entrevistas abiertas y a profundidad. Se aplicó la matriz de marco lógico y los constructos de cuidado émic, é… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…The problems of the feet need another type of attention and, thus, basic care must be part of the routine. However, in occasions, nurses are not aware of this; in addition are scant health workers that realize measure of prevention of the diabetic neuropathy, do not even examine the feet of the persons [52][53][54][55][56][57] .…”
Section: Beliefs and Practices On The Diabetic Footmentioning
confidence: 99%
See 4 more Smart Citations
“…The problems of the feet need another type of attention and, thus, basic care must be part of the routine. However, in occasions, nurses are not aware of this; in addition are scant health workers that realize measure of prevention of the diabetic neuropathy, do not even examine the feet of the persons [52][53][54][55][56][57] .…”
Section: Beliefs and Practices On The Diabetic Footmentioning
confidence: 99%
“…As for the causes of diabetic foot it was found that the majority attribute it to being hit on the feet, walking barefoot, cutting the nails incorrectly, poke it with a nail, or not taking care of themselves properly. However, the knowledge of the risk factors for the diabetic neuropathy is limited, which impedes the suitable prevention of diabetic foot because it does not reach to assume healthily conducts for the health protection 55 .…”
Section: Beliefs and Practices On The Diabetic Footmentioning
confidence: 99%
See 3 more Smart Citations